Exit, voice, loyalty, and neglect reactions to frequency of change, and impact of change: A sensemaking perspective through the lens of psychological contract. Issue 4 (6th June 2016) - Akhtar, Muhammad Naseer; Bal, Matthijs; Long, Lirong
Abstract : Purpose: – The purpose of this paper is to examine how frequency of change (FC) in organizations and impact of change (IC) influence the employee behaviors, i.e. exit, voice, loyalty, and neglect (EVLN) through psychological contract fulfillment (PCF) as a mediator. The moderating role of successful past changes (SPC) is also assessed with direct and indirect relations of FC, and IC alongside employees' behaviors. Design/methodology/approach: – Hypotheses were tested among a sample of 398 financial services-oriented non-managerial-level employees in Pakistan. Bootstrapped moderated mediation analyses (using PROCESS macro) were conducted to test the main and moderated mediation effects. The authors ran series of confirmatory factor analyses to validate the distinctiveness of variables and their items in this study. Findings: – The results largely supported the hypotheses. Findings showed that FC is negatively related to loyalty but positively related to exit, voice, and neglect behaviors via contract fulfillment. IC is also found to have negatively related to loyalty but positively related to exit, voice, and neglect via PCF. SPC was found to moderate the relation between FC, IC, and contract fulfillment, as well as the indirect relationship with exit, voice, and neglect through contract fulfillment and negatively between FC, IC, and loyalty through contract fulfillment. The authors found direct interaction effects of FC via SPC in relation to exit and loyalty and also found direct interaction effects of IC via SPC to exit, voice, and loyalty. Research limitations/implications: – The use of cross-sectional research design does not allow conclusions with respect to causality. The most important implication of the study is that employee behaviors following organizational change can best be understood via a psychological contract framework. A future suggestion is to include more organizations based on longitudinal research design with focus on both employee and employer perspective. Practical implications: – This study highlights the importance of employees' behavioral responses and their sensemaking of PCF in a post-organizational change period. Originality/value: – This study empirically investigated the effects of FC, and IC on fulfillment of psychological contract and behavioral responses of employees using a sample of non-managerial employees, and provides new insights into employee behaviors following organizational changes.